Treatment with pirfenidone for two years decreases fibrosis, cytokine levels and enhances CB2 gene expression in patients with chronic hepatitis C - Flores-Contreras, Lucia (BMC Gastroenterol, 2014)
BACKGROUND: The aim of this study was to assess whether two-years treatment with Pirfenidone influences necroinflammation, fibrosis and steatosis, serum levels of TGF-β1, IL-6, TNF-α and CB1 and CB2 gene expression, in patients with chronic hepatitis C (CHC). METHODS: Twenty-eight patients out of 34 with CHC virus infection were enrolled in the study and received Pirfenidone (1200 mg/day) for 24 months. Six patients dropped out after 12 months of PFD. Liver biopsies and serum samples were obtained at the beginning and end of treatment. Modified HAI was calculated. CB1 and CB2 gene expression was correlated with fibrosis progression alongside with necroinflammation and steatosis. TGF-β1, IL-6, TNF-α and liver transaminases were measured in serum at two-months intervals. HCV genotype and viral load were also assessed. Quality of life was evaluated by SF36 questionnaires and the prognosis of disease was assessed with Child-Pugh score. The Wilcoxon test matched-pair signed ranks were used to analyze the outcomes. RESULTS: Intention to treat analyses were performed for biochemistry and clinical parameters. At the end of treatment, necroinflammation grading was reduced in an average of 3.2 points in 82% of patients (p < 0.05) and Ishak’s fibrosis stage decreased 2-points average in 67% of patients (p < 0.05). Steatosis decreased in 61% of patients. IL-6 and TGF-β1 serum levels decreased significantly in 93% and 67% of patients (p < 0.05), respectively, while TNF-α diminished in 47% of patients. ALT and AST tended to normalize in 81% of patients; CB2 mRNA levels increased in 86% and CB1 expression diminished in 29% of patients. Both, quality of life and Child-Pugh score improvements were reported in all patients. CONCLUSIONS: Pirfenidone for two years benefits CHC patients and improves inflammation, fibrosis and steatosis in higher number of patients as previously shown for 12-months treatment with PFD. Additionally, PFD improved TGFβ1 and IL-6 levels and diminished liver expression of anti-fibrogenic receptor CB2. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT02161952. Protocol Registration Date: 06/11/2014.